Societal Impacts of Zoonotic Diseases: Wildlife and Public Health Interactions - Chowdhury, Bulbul Roy; Sinha, Chandrima; Banerjee, Kaushik (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This article reviews the complex relationships between zoonotic diseases, wildlife, and public health while taking cognizance of how human activities such as habitat encroachment, climatic changes, and international trade amplify outbreaks. Zoonotic diseases, or diseases caught from animals, are a significant global challenge in public health. Over 60% of emerging infectious diseases come from wildlife, so zoonotic transmission is a significant threat to society. Diseases can be transferred from a wildlife species to humans directly, indirectly by acting as a carrier of pathogens, contacting humans or consuming animal products. Some of the recently notable examples include COVID-19, avian influenza, and Ebola. Such diseases have dramatically affected health, economic, and social aspects. In addition to the direct health impact, zoonotic disease transmission has profound social implications. Outbreaks cause billions of dollars in economic loss and really do affect industries through trade, tourism, or agriculture. On a societal level, these diseases can disrupt daily life, intensify inequalities, and strain healthcare systems, especially in resource-limited regions. This article highlights the importance of international cooperation, robust public health systems, and sustainable development practices in mitigating the risk of zoonotic disease transmission. By examining available literatures and assessing current policies, we provide recommendations for reducing the societal and public health impacts of wildlife-related zoonotic diseases in a rapidly changing world. This paper critically examines the multifaceted societal impacts of zoonotic diseases, delving into the complex interplay between wildlife, human behavior, and public health systems. It underscores the urgent need for integrated strategies to address the escalating threats posed by human-wildlife interactions and their public health implications.